A Review of Sensing Strategies for Microwave Sensors Based on Metamaterial-Inspired Resonators: Dielectric Characterization, Displacement, and Angular Velocity Measurements for Health Diagnosis, Telecommunication, and Space Applications - Lijuan Su; Javier Mata-Contreras; Paris Vélez; Ferran Martín (International Journal of Antennas and Propagation)
Four sensing approaches for the implementation of microwave sensors based on transmission lines loaded with metamaterial-inspired resonators are considered in this review paper, and examples of applications are pointed out. In all the cases, sensing is based on the effects that the magnitude under measurement causes in the transmission properties of the resonator-loaded line. Such four strategies are (i) resonance frequency variation, (ii) coupling modulation through symmetry disruption (causing variation of the notch depth), (iii) frequency splitting (also exploiting symmetry properties), and (iv) amplitude modulation of a harmonic signal. Such sensors are useful in various scenarios, of interest in fields as diverse as characterization of dielectric materials for communication circuits, medical diagnosis and treatment with microwave technologies, and sensors for space applications, among others.